Rare Presentation of Subclinical Hypothyroidism from a Lingual Thyroid - Windradi, Choirina; Soelistijo, Soebagijo Adi; Mudjanarko, Sony Wibisono; Yusuf, Muhtarum (Journal of the ASEAN Federation of Endocrine Societies, 2022)
The ectopic thyroid is a rare congenital disorder with incidence between 1:3000- 1:300000 although it could present with thyroid dysfunction. Most ectopic thyroid cases are euthyroid, only a few patients are subclinically hypothyroid.1 It is usually aysmptomatic but as the mass increases it can cause obstructive symptoms.2 At the age of puberty, thyroid hormone deficiency causes hypertrophic glands and results in obstructive symptoms. Asymptomatic cases can be monitored with serial exams or receive hormonal therapy with levothyroxine. However, such treatment does not have a good success rate. The reduction in size occurs very slowly, without significant decreases in volume. 1 Therefore, the decision to excise the mass was made for this patient. After surgery, monitoring of symptoms and thyroid hormone levels should be done regularly. Levothyroxine supplementation is recommended to prevent overt hypothyroidism and to suppress production of TSH.3,4